A guide to manpower planning - Bowey, Angela (London Macmillan, 1974)
This book extensively dealt with the issue of manpower planning, it is an outcome of years of teaching experience at the Manchester Business School.
Includes bibliographical references.
ijb, 15/01/2019
Loans
Keywords: Manpower planning; Manpower policy; Employees training; Great Britain